Closed form of function from recursive definition
Define $f(x)$ for positive integer $x$ as $$f(x) = (2^x - 1)^n - \sum_{j = 1}^{x - 1}\binom{x}{j} \cdot f(j)$$where $n$ is some constant and $f(1) = 1$. I want to determine $f(x)$ explicitly. Here is what I was able to do:
$$f(x) - f(x - 1) = (2^x - 1)^n - (2^{x-1}- 1)^n - \sum_{j = 1}^{x - 2}\binom{x - 1}{j - 1}\cdot f(j) - \binom{x}{x - 1}\cdot f(x - 1)$$
I tried evaluating the telescoping series, but it just became extremely complicated and unhelpful. Any ideas on how else I can find $f(x)$ in closed form?
The binomial coefficient-weighted sum on the right-hand side suggests using exponential generating functions. Define $f(0)=0$ and rewrite the given equation as
$$
\sum_{j=0}^k \binom kj f(j) = (2^k-1)^n = \sum_{i=0}^n \binom ni (2^k)^i (-1)^{n-i}
$$
(assuming $n$ is a nonnegative integer).
Multiplying both sides by $x^k/k!$ and summing over $k$ yields the exponential generating function identity
\begin{align*}
\sum_{k=0}^\infty \frac{x^k}{k!} \sum_{j=0}^k \binom kj f(j)
&= \sum_{k=0}^\infty \frac{x^k}{k!} \sum_{i=0}^n \binom ni (2^k)^i (-1)^{n-i} \\
&= \sum_{i=0}^n (-1)^{n-i} \binom ni \sum_{k=0}^\infty \frac{(2^ix)^k}{k!} = \sum_{i=0}^n (-1)^{n-i} \binom ni e^{2^ix}.
\end{align*}
For the left-hand side, we use the fundamental convolution identity
$$
\biggl( \sum_{k=0}^\infty a_k \frac{x^k}{k!} \biggr) \biggl( \sum_{k=0}^\infty b_k \frac{x^k}{k!} \biggr) = \sum_{k=0}^\infty \biggl( \sum_{j=0}^k \binom kj a_j b_{k-j} \biggr) \frac{x^k}{k!}
$$
with $a_j = f(j)$ and $b_j=1$, so that
$$
\sum_{k=0}^\infty \frac{x^k}{k!} \sum_{j=0}^k \binom kj f(j) = \biggl( \sum_{k=0}^\infty f(k) \frac{x^k}{k!} \biggr) \biggl( \sum_{k=0}^\infty \frac{x^k}{k!} \biggr) = e^x \sum_{k=0}^\infty f(k) \frac{x^k}{k!}.
$$
We conclude that
$$
\sum_{k=0}^\infty f(k) \frac{x^k}{k!} = e^{-x} \sum_{i=0}^n (-1)^{n-i} \binom ni e^{2^ix} = \sum_{i=0}^n (-1)^{n-i} \binom ni e^{(2^i-1)x}.
$$
Comparing Maclaurin coefficients then gives
$$
f(k) = \sum_{i=0}^n (-1)^{n-i} \binom ni (2^i-1)^k.
$$
Note that this is consistent with the formulas in Raymond Manzoni's answer.
Conjectured results for the first values of $n$ :
\begin{array} {cc}
n& f(x)\\
1&1\\
2&3^x-2\\
3&7^x-3\cdot 3^x+3\\
4&15^x-4\cdot 7^x+6\cdot 3^x-4\\
5&31^x-5\cdot 15^x+10\cdot 7^x-10\cdot 3^x+5\\
\end{array}
corresponding to Greg Martin's solution!